Calcium signalling Approaches and Findings in the Heart and Blood - Kaestner, Lars.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book combines general concepts and methods to investigate calcium signalling in cells ranging from molecular biology approaches to manipulation of calcium in living cells. The focus within these methods in on the broad range of fluorescence imaging technology, in particular on optical sectioning techniques and fast image acquisition. In addition to these general guidelines there are application examples in a context beyond calcium signalling in two major fields: investigations of isolated cardiac myocytes and red blood cell related research. While the cellular cardiology section provides snapshots of certain calcium signalling aspects, the red blood cell part presents an overview from the functional identification of calcium-channels to a concept of physiological and pathophysiological relevance.
Summary -- Calcium Signalling Methodology -- Calcium Signalling in Cardiac Myocytes -- Calcium Signalling in Red Blood Cells -- Index.
Keywords: Medicine; Human physiology; Cardiology; Hematology; Cytology; Microscopy; Biomedicine; Biomedicine general; Biological Microscopy; Cardiology; Cell Biology; Hematology; Human Physiology